Frailty and associated outcomes and resource utilization following in-hospital cardiac arrest. (1st January 2020) - Fernando, Shannon M.; McIsaac, Daniel I.; Rochwerg, Bram; Cook, Deborah J.; Bagshaw, Sean M.; Muscedere, John; Munshi, Laveena; Nolan, Jerry P.; Perry, Jeffrey J.; Downar, James; Dave, Chintan; Reardon, Peter M.; et al.
Abstract: Background: In-hospital cardiac arrest (IHCA) is common and associated with high mortality. Frailty is increasingly recognized as a predictor of worse prognosis among critically ill patients, but its association with outcomes and resource utilization following IHCA is unknown. Methods: We performed a retrospective analysis (2013–2016) of a prospectively collected registry from two hospitals of consecutive hospitalized adult patients with IHCA occurring on the hospital wards. We defined frailty using the Clinical Frailty Scale (CFS) score ≥5. CFS scores were based on validated medical review criteria. The primary outcome is hospital mortality. Secondary outcomes include return of spontaneous circulation (ROSC), discharge to long-term care, and hospital costs. We used multivariable logistic regression to adjust for known confounders. Results: We included 477 patients, and 124 (26.0%) had frailty. Frailty was associated with increased odds of hospital death (adjusted odds ratio [aOR]: 2.91 [95% confidence interval [CI]: 2.37–3.48) and discharge to long-term care (aOR 1.94 [95% CI: 1.57–2.32]). Compared with patients without frailty, patients with frailty had decreased odds of ROSC following IHCA (aOR 0.63 [95% CI: 0.41–0.93]). No difference in mean total costs was demonstrated between patients with and without frailty (50, 799 vs. 45, 849). Frail patients did have higher cost-per-survivor (947, 546 vs. 161, 550). Conclusions: Frail individuals who experience an IHCA are more likely to die in hospital or be discharged to long-term care, and less likely to achieve ROSC in comparison with individuals who are not frail. The hospital costs per-survivor of IHCA are increased when frailty is present.